Some Sociolinguistic and Morphosyntactic Features in Dumi - Rai, Netra Mani (Gipan, 2017)
Dumi is a less described Kirati language of the Rai group. The word order phenomenon in this language is of SOV pattern. This language exhibits a consistently ergative-absolutive case marking system. Including the glottal stop, there are 26 consonants and seven phonemic vowels in Dumi. The maximum syllable structure is (C1) (C2) (G) V (X), where G is a glide and ‘X’ is a consonant or a vowel. Dumi children are compelled to read and write in Nepali or English. However, the Dumi language will survive if the Dumi people continue to speak, read and write in their mother tongue.